Convivência e alteridade no processo de conhecimento em dança: a abordagem de Marilene Martins no Trans-Forma Centro de Dança Contemporânea - Gabriela Cordova Christofaro (2018)
This thesis deals with the knowledge process in dance developed by Marilene Martins at Trans-Forma Center of Contemporary Dance. Martins is recognized for having founded Belo Horizontes first modern dance school as well as Trans-Forma Experimental Dance Group, which became important references for the development of this art form in Minas Gerais State capital, Belo Horizonte. The objective of this research was an epistemological approach of the Basic Modern Dance Course, understood as enlightening in Martins artistic and pedagogicalproposal. The approach bears a qualitative character, according to Creswell (2014), based on the Genetic Criticism, according to Salles (2008, 2009, 2014). The procedures used were the reference research and the documental analysis, the latter being done as a critical andinterpretative accompaniment of Trans-Formas notebooks, produced by the artists-teachers. In order to analyze the dossier, made up of twenty-three notebooks created by five artiststeachers as well as Marilene Martins manuscripts, an epistemological network was created,comprising the concepts of networking (MUSSO, 2013), creation as a network in process (SALLES, 2014), and the Theory of Autopoiesis, by Maturana and Varela (2001, 2003), as well as modern and post-modern concepts found in authors who ponder about dance, art learning and the contexts of Latin America and Brazil, such as Banes (1987), Coutinho(2008), Coelho (2011), Efland (2008), Harvey (2012), Hutcheon (2014), Jagodzinsky (2008), Louppe (2012), Lyotard (2011), Paz (1984), and Silva (2005).Through the documents it was possible to access contents related to Martins artistic pedagogical approach, as well as the specific piece of writing used to register such contents. Human anatomy, somatic approaches, diverse dance techniques with emphasis on modern dance, rhythmics, and improvisation were identified in the epistemological weaving of the Basic Modern Dance Course. In Martins work we reiterated the emphasis on modern dance referents and verified, fundamentally, the corporal, technical and artistic diversity, which revealed Marilene Martins post-modern attitude. The Modern Dance Basic Course proved correspondent to an autopoietic system, built through the coexistence with the difference, based on experimentation, and favoring an inventive knowledge base.